The Influence of Transformational Leadership, Work Involvement and Self-Efficacy on Job Satisfaction and Employee Performance at PT Trubaindo Coal Mining, West Kutai Regency - Martiah, Martiah; Hidayati, Tetra; Wahyuni, Sri (Journal of Accounting and Finance Management, 2026)
This study aims to analyze the influence of transformational leadership, work engagement, and self-efficacy on job satisfaction and employee performance at PT Trubaindo Coal Mining, West Kutai Regency, with job satisfaction as a mediating variable. This study uses a quantitative approach with an explanatory design. The population in this study were all 142 permanent employees, with a sample of 106 respondents obtained through a purposive sampling technique. Data collection was carried out through questionnaires, while data analysis used the Structural Equation Modeling Partial Least Squares (SEM-PLS) method. The results of the study indicate that transformational leadership, work engagement, and self-efficacy have a positive and significant effect on employee job satisfaction. Furthermore, these three variables also have a positive and significant effect on employee performance. Job satisfaction has been shown to have a positive and significant effect on employee performance and acts as a mediating variable, strengthening the influence of transformational leadership, work engagement, and self-efficacy on performance. These findings indicate that improving employee performance is influenced not only by leadership and work engagement, but also by employee self-confidence and psychological well-being, such as job satisfaction. The implications of this study suggest that companies need to strengthen transformational leadership practices, increase work engagement, and develop employee self-efficacy through training and organizational support. Furthermore, enhancing job satisfaction needs to be a key strategy in human resource management to encourage optimal and sustainable employee performance.